Supplementary Feeding (PMT) And Undernutrition Examination Of Toddlers In The Working Area Of Puskesams Sawah Lebar Bengkulu City - Sari, Alia Pita; Erpina, Erpina; Fitriani, Neni; Febriani, Emi; Aprianti, Delta (Universitas Dehasen Bengkulu, 2025)
Nutritional problems that occur in toddlers can have various negative impacts on the child's subsequent development. The short-term impacts of nutritional problems in toddlers include children experiencing impaired brain development; impaired intelligence levels; impaired physical growth and development; and impaired body metabolism. In addition to the short-term impacts, there are long-term impacts of nutritional problems in toddlers, including decreased cognitive abilities and learning achievement; decreased body immunity, making them susceptible to disease; having a high risk of several diseases such as blood vessel and heart disease, diabetes mellitus, obesity, cancer, stroke, and disability in old age; and suboptimal work quality which will ultimately result in low economic productivity. This activity aims to provide knowledge and understanding of nutrition for toddlers. By using qualitative descriptive methods/data collection by means of interviews, documentation and direct observation. The results of real work lectures to the community increase motivation and awareness in the community to improve malnutrition in toddlers through counseling or health education towards changes in community knowledge about the importance of nutrition for toddlers through a health education approach.